Estratégias de inclusão no trabalho no contexto da saúde mental - Gomes, Jéssica Negri (2024)
Solidarity economy presents itself as a form of resistance against capitalism, seeking the social inclusion of people excluded from the labor market, with pillars based on solidarity, collective work, self-management, and the generation of economic activity. It has been a democratic response from social movements to the crisis caused by capitalist accumulation, mainly guided by the ethics of solidarity. In March 2020, the pandemic caused by SARS-CoV-2 (the etiological agent of COVID-19) reached Brazil, rapidly spreading across the national territory. It brought damage to the lives of the population not only in the area of public health but also in social and economic aspects. In order to meet the minimum needs of the population, the State created some targeted strategies such as emergency aid and social assistance policies. However, what has truly proven to be an alternative to providing much of the subsistence for vulnerable populations are the initiatives of solidarity economy and solidarity networks within their own territories. In addition to solidarity economy initiatives designed as strategies for the social inclusion of people in situations of social vulnerability, including those experiencing mental suffering, there are income transfer programs, which are social policies aimed at combating poverty and reducing inequalities in developing countries. In the municipality of Araraquara, located in the interior of the state of São Paulo, there are two municipal income transfer programs, the "Bolsa Cidadania" and the "Social Inclusion Incentive Program" (PIIS), mainly aimed at guaranteeing the right to a minimum income and providing productive inclusion, alleviating the impact of increased social exclusion in the municipality. This study had general objectives of identifying the expectations of users of CAPS II and CAPS AD regarding possible entry or return to work from the perspective of the Solidarity Economy; and the facilitators and barriers encountered for inclusion in work for participants in income transfer programs. The specific objectives were to investigate the occupational history of CAPS II and CAPS AD users in Araraquara who are eligible for work inclusion and to identify the level of aptitude of these users for collective and self-managed work. This is a field research, exploratory in nature, with a qualitative approach. Nine users of CAPS II and CAPS AD in Araraquara participated in the study, who are eligible for work inclusion and are currently excluded from the labor market, along with two users engaged in the professional training activities provided by the income transfer program "Social Inclusion Incentive Program (PIIS)." For data collection, three instruments were used: a personal and work information protocol for all research participants and two semi-structured interview scripts, one for the group of participants eligible for returning to work and another for the PIIS participant group, as well as a field diary for notes taken during the entire fieldwork. The data collected from the information protocols were analyzed descriptively, and the interview data were subjected to thematic analysis. The results showed that participants had both positive and negative work experiences throughout their lives and face various barriers to inclusion in the labor market. The study revealed that many participants have an aptitude for collective and self-managed work, and contact with the principles of the solidarity economy sharpened the participants' critical perspective on the exploitation derived from the capitalist system. We concluded that the solidarity economy and transfer programs are important strategies for social inclusion through work for people experiencing mental suffering and those who have problematic use of alcohol and other drugs.